Hubungan Keberfungsian Keluarga Dengan Perilaku Self-Injury Pada Remaja - M. Rafly Adam; Dwi Nastiti (Jurnal Psikologi, 2026)
The stage of Young adult development is considered a crucial phase for achieving the ability to establish social relationships. During this time, Young adult will face various problems and pressures in their development, which can lead to several impacts on them, such as feelings of anxiety, insecurity, and depression. This will eventually lead to a desire for self-injury and suicidal thoughts. The purpose of this study is to investigate the relationship between the functioning of the family and the self-injury among a Young adult in Candi Sayang, Sidoarjo. Using a correlational quantitative approach. The participants are teenagers aged 17 to 25, totaling 47 individuals. Data was obtained using measurement tools in the form of a family functioning scale and a self-injury scale, then analyzed using the Product Moment correlation statistical method. The results of the data analysis showed a correlation coefficient of r = -0.96 with a p value of 0.000 (Sig. < 0.05), indicating a significant negative relationship between family functioning and self-injury in Young adult. It can be concluded that the higher the family functioning, the lower the self-injury among young adult. Conversely, if family functioning is low, self-injury tends to be higher.